Benchmarking CGIAR research outputs for availability and accessibility - Arivananthan, M.; Ballantyne, Peter G.; Porcari, Enrica M. (2010)
To better understand ways that CGIAR Centers make their published research outputs available and accessible, a benchmarking study of six Centers was carried out in 2008 and 2009. The study scored several typical ‘pathways’ that could be used to identify and obtain research outputs published in 2006. Results indicate that these outputs are generally available – they can be identified – in various pathways but that they are much less openly accessible in full text. The results also show differences between the approaches of the six Centers, differences in performance between pathways, and differences in the accessibility of different types of outputs.